2014
DOI: 10.1128/jb.01493-14
|View full text |Cite
|
Sign up to set email alerts
|

Streptococcus mutans Extracellular DNA Is Upregulated during Growth in Biofilms, Actively Released via Membrane Vesicles, and Influenced by Components of the Protein Secretion Machinery

Abstract: f Streptococcus mutans, a major etiological agent of human dental caries, lives primarily on the tooth surface in biofilms. Limited information is available concerning the extracellular DNA (eDNA) as a scaffolding matrix in S. mutans biofilms. This study demonstrates that S. mutans produces eDNA by multiple avenues, including lysis-independent membrane vesicles. Unlike eDNAs from cell lysis that were abundant and mainly concentrated around broken cells or cell debris with floating open ends, eDNAs produced via… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

15
287
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 252 publications
(302 citation statements)
references
References 79 publications
15
287
0
Order By: Relevance
“…The present observations on trend of protein concentration was similar to the observations reported by Brown et al, (2014) Liao et al, (2014) reported the presence of DNA in the extracellular vesicles of gram-positive bacteria.…”
Section: Cpa(r)supporting
confidence: 93%
“…The present observations on trend of protein concentration was similar to the observations reported by Brown et al, (2014) Liao et al, (2014) reported the presence of DNA in the extracellular vesicles of gram-positive bacteria.…”
Section: Cpa(r)supporting
confidence: 93%
“…Previous studies have revealed that MV release is conserved in Gram-negative cells and that MVs are associated with virulence factor delivery, protein secretion, cell-cell communication, protection from phage infection, and other biological processes (2,8). Although Gram-positive bacteria have no outer membrane and are covered by a rigid, thick cell wall, MV production was observed in many Gram-positive bacteria, such as Bacillus subtilis, Staphylococcus aureus, Listeria monocytogenes, Streptococcus mutans, S. pneumoniae, Mycobacteria spp., and Lactobacillus rhamnosus (14)(15)(16)(17)(18)(19)(20)(21). In addition, Grampositive bacterial MVs have been reported to deliver virulence factors to host cells to stimulate an immune response in recipient cells and to facilitate biofilm formation by extracellular DNA release via the MVs (17,22,23), suggesting that functional MV release is also conserved in Gram-positive bacteria.…”
mentioning
confidence: 99%
“…Although Gram-positive bacteria have no outer membrane and are covered by a rigid, thick cell wall, MV production was observed in many Gram-positive bacteria, such as Bacillus subtilis, Staphylococcus aureus, Listeria monocytogenes, Streptococcus mutans, S. pneumoniae, Mycobacteria spp., and Lactobacillus rhamnosus (14)(15)(16)(17)(18)(19)(20)(21). In addition, Grampositive bacterial MVs have been reported to deliver virulence factors to host cells to stimulate an immune response in recipient cells and to facilitate biofilm formation by extracellular DNA release via the MVs (17,22,23), suggesting that functional MV release is also conserved in Gram-positive bacteria. In Gram-negative bacteria, MV production is stimulated by accumulation of the unnecessary proteins in the periplasm, charge repulsion, and the SOS response (8,24).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Filamentous appendages are also observed in other bacteria, for example, outer membrane vesicles (OMVs) on Myxococcus xanthus (42), nanofibers on Streptococcus mutans (43), and rigid nanowires on Shewanella oneidensis (44). Rigid nanowires, which are quite similar to E. tarda EseB filaments in morphology and distribution, are electrically conductive in direct response to electron acceptor limitation (44).…”
Section: Discussionmentioning
confidence: 99%